Influence of political socialization agents on Pakistani youth’s political participation: the mediating role of media and interpersonal communication - Sumera Memon,; Mohd Sobhi Ishak,; Norsiah Abdul Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Apathetic and disconnected from the political world, these are just two of the titles scientists, journalists and politicians have been attributing to youth. Hence, what factors weaken or encourage youth to participate in politics is forefront in academic and non-academic researches. Hence, in view of this context, the role of political socialization agents in engendering political activities among youth cannot be overstated. However, not much research is being carried out in this area. Thus, this study assessed the influence of family communicative environment and peer norms as political socialization agents on media and political participation. A cross-sectional survey was conducted on social sciences students of Pakistani universities. Questionnaire (228) was used to collect data which were analyzed by using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings revealed that among other political socialization agents, peer norms was found to be more significant for youth’s media consumption and political behavior. In particular, results revealed that information consumption through traditional newspaper; TV and online newspaper led to political participation, centering political expression via interpersonal communication. Moreover, interpersonal communication is found to have direct influence on Pakistani youths political participation. This study provides an empirical justification for the potential of peer group as agent of political socialization for enhancing political activities among youth in Pakistan.